Whales : diving into the unknown - Zakroff, Casey (Science comics (First Second (Firm)), 2021)
Dive deep with Science Comics: Whales, a new and exciting volume of First Second's nonfiction graphic novel series! In this volume, Zip, an enthusiastic beaked whale, is eager to share everything he can about whale pods by broadcasting his very own undersea podcast! He will travel across the global ocean interviewing a diverse assortment of whales and dolphins about their amazing behaviors and habitats, as well as their interactions with the human world. Can this one small whale tell the story of the whole ocean and the interconnectivity that affects us all?-- Provided by publisher.